PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN KEJAHATAN SEKSUAL BERDASARKAN PERKARA NOMOR: 2343/Pid.Sus/2015/PN Mdn - Dewi Ervina Suryani (jurnal.unprimdn.ac.id, 2020)
The enactment of Law Number 23 of 2002 concerning Child Protection (which has been amended to Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection), as a special legal instrument to protect children from all crimes , including sexual crimes. This legal instrument does not necessarily make children escape the target of sexual predators, because the number of cases of sexual crimes against children has not shown any decline. Children are weak creatures. The weakness of children is not only in terms of physical, the formation of the brain in children is also not fully formed. The child's physical weakness makes the child unable to provide resistance when experiencing harsh treatment that hurts his body. The imperfect formation of the brain in children makes children unable to distinguish right from wrong, and tends to imitate people's actions. This child's weakness is used by sexual predators to vent their biological desires.